Identification and detection of indoxacarb resistance mutations in the para sodium channel of the tomato leafminer, Tuta absoluta. Issue 8 (20th February 2017) - Roditakis, Emmanouil; Mavridis, Konstantinos; Riga, Maria; Vasakis, Emmanouil; Morou, Evangelia; Rison, Jean Luc; Vontas, John
Abstract: BACKGROUND: Indoxacarb is an important active ingredient extensively used for the control of Tuta absoluta, a major tomato pest, playing a particular role in insecticide resistance management schemes. RESULTS: Reduced susceptibility to indoxacarb was identified (1794‐fold resistance) through toxicological bioassays in a field population from Greece and evolved rapidly to resistance after short laboratory selection. Combined bioassays with synergists and biochemical analysis suggested only a partial involvement of detoxification enzymes in the resistant phenotype. To investigate the role of target‐site resistance, segment 6 of domain IV of the sodium channel in T. absoluta was cloned and the sequences compared between susceptible and indoxacarb‐resistant T. absoluta insects. The presence of the F1845Y and the V1848I indoxacarb resistance mutations was detected and was strongly associated with the phenotype. These amino acid substitutions correspond to recently characterised indoxacarb resistance mutations in diamondback moth ( Plutella xylostella ). Robust and accurate PCR‐RFLP assays were subsequently developed and successfully validated for detecting both indoxacarb resistance mutations in field T. absoluta populations. CONCLUSION: The identification of indoxacarb resistance mutations and the development of diagnostic tools will allow early detection of indoxacarb resistance, facilitating implementation of appropriate resistance management strategies, thus delaying the spread of resistance. © 2016 Society of Chemical Industry